P-350 Endometrial receptivity analysis (ERA) and microbiome testing for recurrent implantation failure (RIF): a matched case control study. (30th June 2022) - Bamford, T; Polson, D; Lowe, P; Easter, C; Coomarasamy, A
Abstract: Study question: Does the use of ERA, EMMA (endometrial microbiome metogenomic analysis) or ALICE (analysis of infectious chronic endometritis) improve implantation rate and clinical pregnancy? Summary answer: The use of ERA significantly improves the clinical pregnancy rate in women with recurrent implantation failure, no difference was observed for EMMA or ALICE. What is known already: The ability of ERA to utilise endometrial tissue transcriptomics to detect asynchronous cycles is controversial. Retrospective studies have demonstrated significantly lower implantation rates for the non-receptive cohort and improved pregnancy rates by personalising the embryo transfer (pET). An RCT reported comparable clinical outcomes for pET and standard FET. There have also been multiple reports of the endometrium being dominated by Lactobacillus, prevalence of this species without bacterial vaginosis leads to positive outcomes in IVF. That said, there is a scarcity of good quality evidence to advocate the use of antibiotics and/or probiotics to treat dysbiosis or pathogens in the subfertile population. Study design, size, duration: From Jan 2017 to August 2021 202 patients underwent one or more of ERA (n = 202), EMMA (n = 101), and/or ALICE (n = 97) at CARE Fertility UK. The cycle subsequent to the test was compared to 404 age matched control cycles. Participants/materials, setting, methods: This study included patients from all 22 clinics across CARE Fertility UK. Rates of positive pregnancy test and clinical pregnancy were compared between patients with normal and abnormal test results using Chi-squared statistic. Binary logistic regression analysis and odds ratios were used to test for improvements in clinical outcomes by adjusting for the following covariates: age, BMI, parity, 2 or more previous implantation failures, donor eggs and frozen embryos. Main results and the role of chance: ERA testing resulted in a normal result in 42.3% of patients, 30.6% were pre-receptive and 17% were early receptive. EMMA resulted in a normal result in 36% of patients, 22% were abnormal, 17% had ultra-low biomass and 25% mild dysbiosis. Only 4% of patients using the ALICE tested positive, therefore this was not included in any modelling due to low event rates. The implantation rate and clinical pregnancy rates showed no statistical significance between those with an abnormal result vs. those who had a normal test. When comparing those tested to matched controls and adjusting for the above covariates, the use of the ERA test was significantly associated with improved implantation rate (OR 3.08, 95% CI 1.57-6.03, p = 0.001) and clinical pregnancy rate (OR 2.7, 95% CI 1.38-5.28, p = 0.004). The use of the EMMA test did not improve implantation (OR 0.42, 95% CI 0.051-3.437, p = 0.418) or clinical pregnancy rate (OR 0.48, 95% CI 0.039-5.89, p = 0.566). When comparing those with an abnormal ERA (i.e. presumed intervention) to matched controls the ERA test was significantly associated with improved clinical pregnancy (OR 5.4, 95% CI 2.007-14.85, p < 0.001). On the other hand, EMMA was not associated with any improvements (p = 1.0). Limitations, reasons for caution: The data collection process had limitations since minimal information was available for patients who underwent previous cycles at other clinics. The number of patients with receptive ERA and abnormal EMMA is small (n = 25) vs. those with a normal EMMA and ERA (n = 10). Therefore, a significant limitation is sample size. Wider implications of the findings: ERA can be more confidently offered to patients and has been demonstrated to significantly improve clinical pregnancy rates. Further research is needed before we can determine whether EMMA or ALICE is a useful test, particularly when considering very few patients show evidence of chronic endometritis. Trial registration number: Not applicable